1993
DOI: 10.1111/j.1365-246x.1993.tb01492.x
|View full text |Cite
|
Sign up to set email alerts
|

The Macquarie Ridge earthquake of 1989

Abstract: S U M M A R YA study of the seismicity on the central portion of the Macquarie Ridge before and after the 1989 May 23 Macquarie Ridge earthquake (Mw = 8.2) and the solution of the inverse problem to obtain the moment release time history during the earthquake are presented. The aftershock study shows that there were remarkably few and small aftershocks on the main fault. The aftershocks were distributed along a 220 km portion of the India/Australia-Pacific plate boundary and indicate that the motion was bilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 27 publications
3
48
0
Order By: Relevance
“…It led to the characterization of barriers as being material (large S) or geometrical (when the fault plane deviated from planarity) by AKI (1979). It has led to the identification of barriers in the field by structural geologists and by seismologists in various locations world wide (LINDH and BOORE, 1981;KING and YIELDING, 1984;NABELEK and KING, 1985;SIBSON, 1986;BARKA and KADINSKY-CADE, 1987;BRUHN et al,1987;DAS, 1992DAS, , 1993HENRY et al, 2000, to name only a few among many such examples). Finally, the most convincing evidence that faults are heterogeneous not only near the surface of the Earth but also at the depths where the main faulting in an earthquake occurs is that aftershocks do occur at these depths.…”
Section: Complex Faulting Modelsmentioning
confidence: 99%
“…It led to the characterization of barriers as being material (large S) or geometrical (when the fault plane deviated from planarity) by AKI (1979). It has led to the identification of barriers in the field by structural geologists and by seismologists in various locations world wide (LINDH and BOORE, 1981;KING and YIELDING, 1984;NABELEK and KING, 1985;SIBSON, 1986;BARKA and KADINSKY-CADE, 1987;BRUHN et al,1987;DAS, 1992DAS, , 1993HENRY et al, 2000, to name only a few among many such examples). Finally, the most convincing evidence that faults are heterogeneous not only near the surface of the Earth but also at the depths where the main faulting in an earthquake occurs is that aftershocks do occur at these depths.…”
Section: Complex Faulting Modelsmentioning
confidence: 99%
“…On the other hand, the inverse problem for the earthquake source is intrinsically very unstable (Kostrov & Das 1988), and until very recently, sufficiently high‐quality seismograms and with sufficiently good spatial coverage were not available for a reliable estimate of the fault dimensions of the main shock. Even for an M w =8.0 earthquake as recently as 1989 (the Macquarie Ridge earthquake), Das (1993) showed that the teleseismic seismograms were unable to constrain the fault area, and aftershocks had to be used to constrain it a priori . The 1998 Antarctic earthquake is the first one for which the seismograms did constrain the fault rupture area (Henry et al 2000), and hence this is a very promising tool for future global studies.…”
Section: Introductionmentioning
confidence: 99%
“…Recent submarine earthquakes, which initially appeared not to be related to such planes of weakness, were, after detailed investigation, found to lie on old spreading ridges and fossil fracture zones. Some aftershocks of the great 1989 Macquarie Ridge earthquake [Das, 1992[Das, , 1993, earthquakes in the Tasman Sea [Valenzuela and Wysession, 1993], and the 1987-1992 Gulf of Alaska earthquakes [Pegler and Das, 1996] fall in this category.…”
Section: Introductionmentioning
confidence: 99%